“New Mediterranean Biodiversity Records” 2019 - N. STERN; A. BADREDDINE; G. BITAR; F. CROCETTA; A. DEIDUN; B. DRAGIČEVIĆ; J. DULČIĆ; H. DURGHAM; B.S. GALIL; M. GALIYA; S. IKHTIYAR; A. IZQUIREDO-MUÑOS; et al. (Mediterranean Marine Science, 2019)
This is the second collective paper issued in 2019, currently amalgamates new knowledge on the Mediterranean geographic distributions of 17 species from five phyla (six aliens, three cosmopolitans, two east Atlantic records and six natives). The acknowledged species were reported from ten countries, mentioned here from west to east: Spain: first report of the east Atlantic grouper Cephalopholis taeniops in the western Mediterranean and an inclusion of Pontarachna puntulum and Litarachna communis to the pontarachnid fauna of Spain; Morocco: first record of Solea senegalensis from the Moroccan Mediterranean coast; Algeria: a valid confirmation for the presence of Sardinella maderensis; Malta: a first record of the Red Sea stomatopod Erugosquilla massavensis; Italy: a rare observation of the crab Paragalene longicrura from Siciliy and a further integration of the alien brown shrimp Penaeus aztecus to the commercial catch in Sicily; Montenegro: a first record of the Lessepsian bigfin reef squid Sepioteuthis lessoniana from the Adriatic Sea; Turkey: northernmost documentation of the Mediterranean flatworm Prostheceraeus giesbrechtii in the Aegean Sea; Israel: a solid confirmation for the population establishment of both the alien rock shrimp Sicyonia lancifer and two species of angelfish, and a first and deepest record of the crystalline goby Odondebuenia balearica; Lebanon: first record of the jellyfish Pelagia noctiluca; Syria: first records of the crown jellyfish Nausithoe punctate and the smallscale codlet Bregmaceros nectabanus.

Assessment of goods and services, vulnerability, and conservation status of European seabed biotopes: a stepping stone towards ecosystem-based marine spatial management - M. SALOMIDI; S. KATSANEVAKIS; A. BORJA; U. BRAECKMAN; D. DAMALAS; I. GALPARSORO; R. MIFSUD; S. MIRTO; M. PASCUAL; C. PIPITONE; M. RABAUT; V. TODOROVA; et al. (Mediterranean Marine Science, 2012)
The goal of ecosystem-based marine spatial management is to maintain marine ecosystems in a healthy, productive and resilient condition; hence, they can sustainably provide the needed goods and services for human welfare. However, the increasing pressures upon the marine realm threaten marine ecosystems, especially seabed biotopes, and thus a well-planned approach of managing use of marine space is essential to achieve sustainability. The relative value of seabed biotopes, evaluated on the basis of goods and services, is an important starting point for the spatial management of marine areas. Herein, 56 types of European seabed biotopes and their related goods, services, sensitivity issues, and conservation status were compiled, the latter referring to management and protection tools which currently apply for these biotopes at European or international level. Fishing activities, especially by benthic trawls, and marine pollution are the main threats to European seabed biotopes. Increased seawater turbidity, dredged sediment disposal, coastal constructions, biological invasions, mining, extraction of raw materials, shipping-related activities, tourism, hydrocarbon exploration, and even some practices of scientific research, also exert substantial pressure. Although some first steps have been taken to protect the European sea beds through international agreements and European and national legislation, a finer scale of classification and assessment of marine biotopes is considered crucial in shaping sound priorities and management guidelines towards the effective conservation and sustainability of European marine resources.

Limited trophodynamics effects of trawling on three Mediterranean fishes - F. Badalamenti; C. J. Sweeting; N. V. C. Polunin; J. Pinnegar; G. D’Anna; C. Pipitone (Marine Biology, 2008)